Android-Based Comics: An Alternative Media to Improve Scientific Literacy - Listianingsih, Mardianti; Astuti, Irnin Agustina Dwi; Dasmo, Dasmo; Bhakti, Yoga Budi (Jurnal Penelitian dan Pembelajaran IPA, 2021)
The students’ scientific literacy nowadays is relatively low because the lack of media learning to improve scientific literacy. This research aimed to test the feasibility of developed Android-based comics on material style and motion to scientific literacy. This study used a research and development using ADDIE (analysis, design, development, implementation, evaluation) model. The subject of this research is students from grade VIII at one of the junior high school in Indonesia. The instruments of this research are validation sheets and student response sheets. The result of validation test in term of material expert acquired on average percentages of 93.26% and media experts at 97.08%. Moreover, the pretest of students' scientific literacy is 2.26, and the post-test of students' scientific literacy is 3.40, with the N-gain formula obtained a value of 0.72 with the category "High". Based on these results, it can be concluded that the developed Android-based comics as an alternative media are worthy to be used according to expert recommendation and students’ responses. Android-based comics can be used to improve students’ scientific literacy. The implications for future teaching appear to be that Android-based comics have clear value as an innovative tool.